Influence of Water Quality Parameters on Zooxanthellae Density in Reef-Building Corals from Pahawang Island, Lampung, Indonesia - Anugerah, Nanda Rizky; Aryawati, Riris; Isnaini, Isnaini; Ulqodry, Tengku Zia; Hendri, Muhammad; Suteja, Yulianto (Jurnal Biologi Tropis, 2026)
Despite the ecological and economic significance of coral reefs, quantitative data on how water quality parameters regulate zooxanthellae density in anthropogenically impacted tropical reefs remain limited. This study investigated the influence of water quality parameters on zooxanthellae density in branching corals at Pahawang Island, Lampung, Indonesia, across four stations representing different levels of human disturbance: dock area (Station 1), floating net cages area (Station 2), recreational area (Station 3), and a relatively pristine area (Station 4). Coral fragments were collected by SCUBA diving at 2–5 m depth, and zooxanthellae were extracted by homogenization followed by centrifugation, with cell density quantified using a hemocytometer under light microscopy. Physical and chemical water quality parameters were measured in situ using a CTD profiler, while nutrient concentrations were analyzed according to SNI protocols. Zooxanthellae density ranged from 16,822 to 22,227 cells/cm², indicating a healthy symbiotic status across all stations. Principal Component Analysis (PCA) identified dissolved oxygen (5.5–6.4 mg/L), depth (2.20–4.10 m), and water clarity (2.0–3.0 m) as the primary environmental drivers of zooxanthellae density variation, while temperature, pH, and salinity remained stable and within coral-suitable ranges. Hydrodynamic conditions and oxygen availability, rather than nutrient enrichment, appear to be the dominant regulators of zooxanthellae density at this site. These findings highlight the need for site-specific management strategies that prioritize maintaining dissolved oxygen levels and water circulation, and provide a scientific basis for developing zoning policies in coral ecotourism areas of Pahawang Island to ensure long-term reef ecosystem health.